Intrinsic risk factors of non-contact quadriceps and hamstring strains in soccer: a prospective study of 100 professional players - Fousekis, K.; Tsepis, E.; Poulmedis, P.; Athanasopoulos, S.; Vagenas, G. (British Journal of Sports Medicine, 2010)
Objectives: To identify the intrinsic risk factors of non-contact strains in the hamstrings and quadriceps muscles of professional soccer players via a cohort prospective design.